ANALISIS USAHATANI PADI SAWAH (Oryza sativa L.) di DESA BERUGE KECAMATAN BABAT TOMAN KABUPATEN MUSI BANYUASIN - lestari, Endang; Fitriyana, Gusti (Paradigma Agribisnis, 2024)
Rice Farming Analysis (Oryza Sativa L.) in Beruge Village, Babat Toman District, Musi Banyuasin Regency, South Sumatra Province. This research aims to determine the amount of income and level of profit from rice farming in Beruge Village, Babat Toman District, Musi Banyuasin Regency. The sampling method used was simple random sampling. The results of the study show that the total cost incurred to carry out wetland rice farming in one planting season period is IDR 4,854,763. Revenue is influenced by the selling price of rice production, with a total revenue of IDR 12,433,625. The total income obtained from rice farming is IDR 7,991,636. The R/C ratio value for rice farming at the research location is 2.74, meaning that for every IDR 1 of cost incurred, a revenue of IDR 2.74 is obtained. This indicates that the R/C ratio is more than one, so that wetland rice farming in Beruge Village is profitable and worth cultivating. In addition, the analysis results also show that rice farming in Beruge Village has good prospects for further development. This is supported by the available land potential, suitable climatic conditions, and the local government's commitment to encouraging increased rice production in the region. Thus, rice farming in Beruge Village can become one of the main sources of income for the local community and contribute to food security in Musi Banyuasin Regency